Service Quality, Customer Satisfaction and Loyalty: An Empirical Analysis of Banking Sector in Pakistan - Zafar, Mohsin; ., Aasia Asif; ., Ahmed Imran Hunjra; ., H. Mushtaq Ahmad (Information Management and Business Review, 2012)
The basic aim of this study is to explore most common constructs for quality of banking services, which influence customer satisfaction and examine the impact of customer satisfaction on customer loyalty in the context of banking relationships. The questionnaire was used to collect the data from 192 valid respondents by convenience sampling method. SPSS was used to analyze the data and AMOS was used to test the model. The results of the study show that there is a positive and significant link between customer satisfaction and constructs of service quality like tangibility, reliability, competence conflict handling and further study inferred that customer satisfaction is positively significant related to customer loyalty.